Diversidade antigênica de isolados brasileiros de pestivírus hobi-like - Dias, Raissa Kuntz (2018)
Bovine viral diarrhea virus (BVDV) is a major pathogen of bovine herds and it is distributed globally, causing important economic losses to the cattle industry. The genus Pestivirus of the family Flaviviridae is composed by four viral species: bovine viral diarrhea virus 1 and 2 (BVDV-1 and BVDV-2), border disease virus (BDV) and classical swine fever virus (CSFV). A fifth species has been proposed (atypical pestiviruses, HoBi-like pestiviruses or BVDV-3), due to their genetic and antigenic differences in relation to BVDV species. These viruses were originally identified in fetal bovine serum from Brazilian origin and, subsequently, isolated from diseased animals in several countries. Herein we performed an antigenic characterization of eight Brazilian HoBi-like viruses isolated from persistently infected (PI) animals and from gastroenteric disease (2007 to 2015). Phylogenetic analysis based on the 5’ unstranslated region (UTR) clustered these viruses with other HoBi-like viruses from European and Asiatic origin. Monoclonal antibody (mAb) binding indicated variability in the Hobi-like virus glycoprotein E2 and significant differences from the homologous BVDV-1 and BVDV-2 glycoprotein. Analysis of antigenic relatedness based on virus-neutralizing titers using virus-specific antisera revealed that HoBi-like viruses are antigenically very different from BVDV-1 and, to a lesser extent, from BVDV-2. Cross-neutralizing assays between pairs of HoBi-like viruses and their respective antisera indicated the existence of antigenic variability among these viruses, even for viruses isolated from the same herd in different occasions. Moreover, the identification of a HoBi-like isolate with low antigenic similarity with the other isolates indicates the potential existence of antigenic subgroups among HoBi-like virus isolates. Finally, sera of lambs immunized with commercial BVDV vaccines showed low or undetectable neutralizing activity against HoBi-like isolates. These results indicate significant antigenic differences between BVDV genotypes and Brazilian HoBi-like viruses and the existence of antigenic variability within this atypical group of pestiviruses. These findings extend the knowledge about the antigenic diversity of HoBi-like viruses and reinforce the need for their inclusion in current BVDV vaccines.